Modifying food texture. Volume 2, - Chen, Jianshe; Rosenthal, Andrew J. (Woodhead Publishing is an imprint of Elsevier, 2015)
Modifying Food Texture, Volume 2: Sensory Analysis, Consumer Requirements and Preferences explores texture as an important aspect of consumer food acceptance and preference, specifically addressing the food textural needs of infants, the elderly, and dysphagia patients. This volume covers the sensory analysis of texture-modified foods, taking an in-depth look at the product development needs of consumers and exploring the sensory analysis of food texture and the development of texture-modified foods. Explores texture as an important aspect of consumer food acceptance and preferenceAddress.
Keywords: Food texture.; Food -- Biotechnology.; Food additives.; Food industry and trade.; elektronické knihy; electronic books